PENGARUH IMPLEMENTASI KEBIJAKAN RESTRUKTURISASI TERHADAP EFEKTIFITAS ORGANISASI DI SEKRETARIAT DAERAH KOTA MANADO - KAIRUPAN, GABRIELA; MANDEY, JANTJE; RURU, JOORIE (Sam Ratulangi University, 2014)
ABSTRAK In correlation with that problem this research has been focused to answer how far the effectsof implementation of restructure policy toward organization affectivity in the secretariat of Manadodistrict. The method that will be used in this research is quantitative; the source of data for this researchcomes from 35 random people of civil servant from 186 people whom work in secretariat of Manadodistrict. Data collection method using questioner and add with interview. This research using frequencydistribution and percentage, linier regression and moment product correlation as analysis technic.Yet, based on the previous study, showing that the performance of duty and function of district secretarynot showing optimal result as a whole. Based on the concession from couple of structural officials andmanaging employee that have been interviewed in previous survey looks like not all the program and eventthat have been decided could achieved maximal results as decided in strategic planning, the fact itselfcould indicate that the restructure policy implementation not optimally could form organization affectivity.To understand the correlations of functional/effect of restructure policy toward organizational affectivityin Manado city secretariat district officeTo understand the correlation and determination or the size ofinfluence of restructures policy implementation toward organizational affectivity in Manado citysecretariat district office. Based on the result can be concluded that: restructure policy implementation oforganization has a functional correlation or positive affect and very significant toward the affectivity oforganization in Manado city secretary of district office. Restructure policy implementation of organizationhas caused the increase of significance organization affectivity in Manado city secretary of district office.It could portrays how restructure policy of organization of district instruments as described in PP 41 inyear 2007, have given positive impact and result toward the increase of district instruments affectivity.Keyword : Implementation of restructure, organization affectiv ty